Islamic Education by Badiuzzaman Said Nursi in Secularic Period of Turkey - Nur Kholis (IAIN Salatiga, 2018)
This research discusses the role of Badiuzzaman Said Nursi in the islamic education happened in Turkey during the secularic period in the year of 1924 to 1950. This is a library reseacrh with the historical method of analysis through the literature study and documentation of the works of Badiuzaman Said Nursi and another supporting literature. From the research obtained the information that Badiuzzaman Said Nursi plays the important role for giving the islamic education during the secularic period in Turkey. In addition, Badiuzzaman Said Nursi also creates a work under the title Risalah Nur to perform the islamic education during the secularic period. The Risalah Nur contains the education of tauhid, qur’anic interpretation and the fundamental rules of islam that successfully educate the people to secure the faith from the secularism.